Analysis of Wordwall-Based Gamification Design in Science Learning on Force and Motion Material - Juan, Fransiskus Andi; Ki'i, Oktavianus Ama; Panis, Isabel Coryunitha (Indonesian Journal of Instructional Media and Model, 2025)
In the digital learning era, integrating technology into the classroom is essential to enhance student engagement and improve learning outcomes. One widely used platform is Wordwall, which enables the creation of interactive and gamified learning activities. This study aims to examine the feasibility of a gamification-based learning design using Wordwall for teaching science topics, specifically force and motion. The research employed a descriptive quantitative method, involving 19 students from class VII B as the sample. Data were collected through observation, validity testing, and reliability testing. The validity assessment yielded a score of 67, indicating that the gamification design is feasible for classroom use. Furthermore, the reliability test showed a consistency level of 89.38 percent, demonstrating high reliability of the learning media. These findings suggest that the Wordwall-assisted gamification learning design is both valid and reliable for supporting science education on force and motion. The study contributes to the growing body of research on educational technology by providing empirical evidence of the effectiveness of gamified digital tools in enhancing learning experiences.